A complementary currency system in Palestine : concept, implementation issues and challenges - Altarturi, Basheer Hussein Motawe (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2021)
The Palestinian people, under the Paris Protocol, are debarred from issuing their own money and is forced to remain dependent on the Israeli new shekel and other externally issued currencies. The absence of a Palestinian currency deprived Palestine of the ability to set its monetary policy, causing an inflationary system. Therefore, the primary goal of this study is to undertake an economic analysis of the viability of implementing the complementary currency in Palestine. The proposed complementary currency aims to provide a reliable monetary system able to guarantee price stability. To ensure price stability over the long run, this study constructs an index for a basket of commodities as a “money of account” of the complementary currency for Palestine economy. To strengthen the relative price of “money of account” as a way to stabilise the level of the prices, there should be a link between the price and “money of account” that includes a wide variety of goods and possibly services. Therefore, the proposed complementary currency will be backed up by 16 main export products of Palestine, which they represent 75% of total Palestine exports. Selected 16 commodities are aluminium and its articles, building stone, electrical machinery, flours and cereals, footwear, furniture, fruits, medicaments, milk and dairy products, olive oil, iron and steel and their articles, paper and printed material, plastic and its articles, textile and clothing, vegetables, and wood. GARCH models are applied to test of the volatility of the index of “money of account” of the complementary currency to assess price stability of proposed complementary currency in the long run. Finally, to verify the viability of the implementation of the proposed complementary currency in Palestine, this study adopts the theory of planned behavioural with adding facilitating condition, complexity and trust to the model. The volatility analysis obtained by appropriate symmetric and asymmetric GARCH family models showed that the index of “money of account” of commodities basket is stable in the long run. The results reported insignificance of the constant, i.e. (μ) and (ω), ARCH-in-Mean and asymmetry effect, i.e. (γ_1), which indicates the absence of abnormal returns, lack of risk-return trade-off phenomenon, and the absence of the leverage effects in the index of “money of account” of commodities basket, respectively. To analyse the viability of implementing the complementary currency in Palestine, the study adopts a structural equation modelling. The findings show that attitude, subjective norms, facilitating conditions and trust have a significant positive influence on the behavioural intention. Complexity has a significant negative influence on behavioural intention. Only perceived behavioural control shows an insignificant effect on behavioural intention. This research has expanded the knowledge base of complementary currencies as a tool for price stability over the long term. The findings of this study can assist decision-makers in Palestine to develop a complementary currency based on the blockchain technology to rebuild a local economy and to provide a reliable monetary system able to guarantee price stability and lessen the costs and damages associated with various Israeli policies have been forced in Palestine. Although, this study aimed to design complementary currency's “money of account” in Palestine; the proposed model did not discuss on the mechanism of the system and how it will be implemented technically and legally. Future research is recommended to overtake the technological implementation, such as blockchain technology and cryptocurrency, of the proposed system and legal issues.